2012
DOI: 10.1021/jp302478a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Water Facilitates Energy Transfer by Inducing Extended Vibrations in Membrane Lipids

Abstract: ABSTRACT:We report the complete assignment of the vibrational spectrum of dipalmitoylphosphatidylcholine (DPPC), which belongs to the most ubiquitous membrane phospholipid family, phosphatidylcholine. We find that water hydrating the lipid headgroups enables efficient energy transfer across membrane leaflets on sub-picosecond time scales. The emergence of spatially extended vibrational modes upon hydration, underlies this phenomenon. Our findings illustrate the importance of collective molecular behavior of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The approach could also be combined with more accurate simulation of bilayers. Full atomistic simulations and in particular ab initio simulations, could in principle provide more accurate descriptions of the system but comes with a huge computational burden (Mashaghi et al, 2012, 2013a). …”
Section: Resultsmentioning
confidence: 99%
“…The approach could also be combined with more accurate simulation of bilayers. Full atomistic simulations and in particular ab initio simulations, could in principle provide more accurate descriptions of the system but comes with a huge computational burden (Mashaghi et al, 2012, 2013a). …”
Section: Resultsmentioning
confidence: 99%
“…14,16 The calculated ground state structure is used as the starting configuration for AIMD and AIMC simulations at 300 K (Figure 1a). The AIMD simulations are performed 14,19,20 up to a time of 3 ps with a time step Δt = 0.1 fs, which is about one hundredth of the shortest vibration period in this system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The AIMD simulations are performed 14,19,20 up to a time of 3 ps with a time step Δt = 0.1 fs, which is about one hundredth of the shortest vibration period in this system. 16 The temperature is kept fixed with a Nose−Hoover thermostat.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…60 Despite its neutrality, DPPC carries a significant electric dipole moment and surface potential. Mashaghi 61 reported that the lipid headgroups of DPPC tightly bound to interfacial water molecules facilitates energy transfer across membranes 62 . This might explain the antifouling property of DPPC and the dispersion of NPs in DPPC suspension.…”
Section: Discussionmentioning
confidence: 99%